Marketplace Interaktif Jasa IT - Rahmat Riansah Husain; Sitti Suhada; Nikmasari Pakaya (Diffusion: Journal of Systems and Information Technology, 2021)
Limited information is sometimes a problem faced due to the publication of service is only from friends or relatives. Service vendors also have constraints in terms of promotion so that not all people know about vendor information that provides IT services. Preliminary research conducted on 25 respondents regarding IT services in Gorontalo District and Gorontalo City reveals 75% of respondents choose IT service that are often used, such as mobile service, and 64% laptop service. However, the problem is that 64% of respondents state that it is difficult to get information about IT service in Gorontalo District and Gorontalo City. This research aims to build an interactive IT service marketplace application that can help interaction between customers and service vendors. The system development method used is the Prototype method by using the PHP programming languge and the MySQL database. The result of this research is to make customers (user) easier to find information on service vendors, types of services provided, price details, vendor portofolios in the form of images and videos, location in the form of google maps, and to assist service vendors in promoting their services.Keywords: Marketplace, IT Service, Prototype